Potential Utilization of Rice Husk Waste in Making Charcoal Briquettes in Kertamulya Village - Purnama, Fahrul (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Rice husk is an agricultural waste that is still underutilized, even though it has great potential as a raw material for making charcoal briquettes. This study aims to examine the potential for utilizing rice husk as charcoal briquettes and to educate the people of Kertamulya Village about the manufacturing techniques. The method used in this study is a descriptive method with a socialization approach and direct training to the local community. The briquette making process involves several stages, namely burning the husk using the pyrolysis method, mixing with natural adhesives, molding, and drying. The results of the experiment showed that the composition of the mixture of materials and the right drying method greatly affect the quality of the briquettes produced. Briquettes with a ratio of 100 grams of starch, 1 kg of charcoal powder, and 400 ml of hot water gave the best results with stable combustion and long-lasting embers. In addition to contributing to reducing agricultural waste, this innovation also has economic value by opening up business opportunities for the community. Therefore, the use of rice husk as charcoal briquettes can be an environmentally friendly and sustainable alternative solution in supporting energy security and the welfare of rural communities.